Implementasi Total Quality Management (TQM) Dalam Peningkatan Mutu Lulusan Melalui Bimbingan Konseling Di SMAN 3 Pasuruan - Wicak Suryatmojo; Zenita Afifah Fitriyani (Journal of Education and Teaching Learning, 2023)
Total Quality Management (TQM) is currently used at every level of education. The existence of the TQM concept can be applied as an alternative solution for improving the quality of graduates at SMAN 3 Pasuruan. The counselor also plays a very large role in supporting the implementation of TQM in improving the quality of graduates, because it can provide information and motivate students to be able to continue their studies to the tertiary level. The purpose of this research is to determine the implementation of TQM in improving the quality of graduates through guidance and counseling. This research method uses a qualitative method with data collection using the Miles and Huberman approach, namely data presentation, data reduction, inference, and verification. The results of the study state that three elements of TQM can be implemented at SMAN 3 Pasuruan, namely customer focus, continuous process improvement, and total involvement and empowerment. This research is expected to help SMAN 3 Pasuruan in improving the quality of graduates by implementing total quality management and role support as well as counselor.